2007
DOI: 10.1111/j.1744-618x.2007.00057.x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Diagnostic Competency and the Analysis of Factors Influencing Competency Using Written Case Studies

Abstract: Many of these Japanese nurses did not perform at satisfactory levels of diagnostic competency with these two written case studies. Factors that influenced diagnostic competency were length of clinical experience, decision-making responsibility, and frequency of studying nursing diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 18 publications
0
35
0
2
Order By: Relevance
“…Written case scenarios have been used in studies in other countries for both nurses and paediatricians working with triage 8 16–21. An important limitation of using this methodology is that it is not assessed whether the nurses ask the patients the proper questions needed to clarify the urgency because the important information is already available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Written case scenarios have been used in studies in other countries for both nurses and paediatricians working with triage 8 16–21. An important limitation of using this methodology is that it is not assessed whether the nurses ask the patients the proper questions needed to clarify the urgency because the important information is already available.…”
Section: Discussionmentioning
confidence: 99%
“…Written case scenarios have been used in several studies to evaluate agreement with national guidelines, and they are regarded as suitable tools in the assessment of clinical competence 8 11…”
Section: Introductionmentioning
confidence: 99%
“…The scale can be used in all clinical settings by nursing students and clinical nurses and is currently used in the US, Brazil, Japan, Spain, and India (Collins, 2013;Hasegawa, Ogasawara, & Katz, 2007;Lunney & Krenz, 1992;Oliva et al, 2005;. The PND is simple to use, fast to administer, highly versatile, and sensitive to small differences in attitude.…”
Section: Introductionmentioning
confidence: 98%
“…Only in the third case study did the students attending the third year outperform the others in the NDxs indicated by the model, which may be related to several variables. The NDx competence may be related to factors such as time of clinical experience, responsibility in decision making, and frequency of study on NDx (Hasegawa, Ogasawara, & Katz, 2007).…”
Section: Discussion/implicationsmentioning
confidence: 99%